2000
DOI: 10.1111/j.1749-6632.2000.tb07021.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biological Determinants of the Cytotoxic Actions of Camptothecins: Perspective for the Development of New Topoisomerase I Inhibitors

Abstract: Camptothecin, originally discovered in 1957 as an antitumor activity in plant extracts, has recently become one of the most promising leads to new anticancer drugs. After lingering for many years, interest in camptothecin was revitalized in 1985 upon discovery of its specific action on topoisomerase I. Detailed elucidation of action mechanisms at the molecular, cellular, and pharmacologic levels has made camptothecin and its congeners perhaps the best understood among clinical anticancer drugs. Promising chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…We noticed that this loss of replication competence during the S phase is followed by a rapid accumulation of DSBs and GCRs and then cell death. It has been demonstrated that CPT can cause the collapse of replication forks (Kohn and Pommier, 2000;Strumberg et al, 2000). DSB generated from such fork collapse is believed to represent the main cytotoxic lesion induced by CPT and its derivatives (Pommier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We noticed that this loss of replication competence during the S phase is followed by a rapid accumulation of DSBs and GCRs and then cell death. It has been demonstrated that CPT can cause the collapse of replication forks (Kohn and Pommier, 2000;Strumberg et al, 2000). DSB generated from such fork collapse is believed to represent the main cytotoxic lesion induced by CPT and its derivatives (Pommier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Only the lactone form is active with respect to inhibition of topoisomerase I. In blood and uids at physiological pH, the α-hydroxy δ-lactone ring moiety hydrolyzes which leads to deactivation of CPTs [5]. The process of deactivation is accelerated in a solution containing albumin.…”
Section: Introductionmentioning
confidence: 99%
“…Camptothecins exist in two forms: lactone, stable at pH<5. 5, and open ring carboxylate, stable at pH>9 (Table I). Only the lactone form is active with respect to inhibition of topoisomerase I.…”
Section: Introductionmentioning
confidence: 99%
“…DNA topoisomerases are nuclear enzymes essential for DNA replication, RNA transcription, chromosomal condensation and mitotic chromatid separation (Caron and Wang, 1993;Gupta et al, 1995;Kohn and Pommier, 2000). There are two major classes of topoisomerases, I and II, in eukaryotic cells.…”
mentioning
confidence: 99%
“…Topoisomerase II functions as a dimer and forms a doublestranded cleavage with each topoisomerase II molecule covalently bound to the 5 0 -terminus of a DNA nucleotide, producing a double-stranded break (Holm et al, 1985). Topoisomerase-targeted agents stabilise a transient covalent enzyme -DNA complex, which produces DNA strand cleavage and apoptosis (Kohn and Pommier, 2000). Preclinical study of the in vivo therapeutic effect of sequential combinations of topoisomerase I-and II-acting drugs in a murine tumour model system reveals that topoisomerase I mRNA and protein levels in the tumour decrease, whereas topoisomerase II mRNA and protein levels rise, after treatment with camptothecins (Eder et al, 1998) and topotecan (Liebes et al, 1998).…”
mentioning
confidence: 99%